QIRĀ’ĀT AL-‘ASYR AN-NĀFĪʻIYYAH (STUDI TENTANG SANAD DAN KONTROVERSI PERAWI IMAM NÂFIʻ) - Muhtadin, Khoirul; Pranata, Sofyan Puji; Mustofa Kamal, Muhammad Ali; Aqdi, Hifdi Salimatul; Permatasari, Oktaviani (Dar el-Ilmi : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2023)
The popularity of qirā’āt al-'asyr an-nāfī'iyyah in Morocco or Moroccan qira'at has recently been interesting to study academically. This research on qira'at or variants of al-Qur'an reading is descriptive qualitative in nature to explain how the history, status and quality of sanad refer to the works used as references for qira'at al-asyr an-nāfī’iyyah, especially the works of ad-Dāni's work. There has not been much research on qira'at, especially conducted by Indonesian academics. This reading is very interesting, although it should not be popularized with the term qira'at or history, but more precisely with the term ṭarīq , because what is called qira'at al-'asyr an-nāfī’iyyah is actually the ten ṭarīq of Imam Nāfi’ through the path of four narrators him, namely Qolun, Warsy, Isma'il and Ishaq. The four narrators and ten tariqs were mentioned by Imam Ad-Dāni in the book at-ta'rif fi ikhtilaf ar-ruwah 'an-nafi. This book is the main reference in taking the sanad qira'at al-'asyr an-nāfī’iyyah. Apart from that, of course there are also other ad-Dāni books that are used as references, such as the al-mufradat as-sab' book. This qira'at is sanad mutawatir according to Moroccan ulama' and has only been studied by students from outside Morocco. Saudi ulama' consider syadz and prohibit using the history of Imam Nāfi’ from other than Qolun and Warsy mentioned by Imam Ad-Dāni in the book at-ta'rif. Meanwhile, some Syrian ulama’ chose tawaquf.